Bank Lines of Credit in Corporate Finance: An Empirical Analysis - Sufi, Amir (Review of Financial Studies, 2009)
[I empirically examine the factors that determine whether firms use bank lines of credit or cash in corporate liquidity management. I find that bank lines of credit, also known as revolving credit facilities, are a viable liquidity substitute only for firms that maintain high cash flow. In contrast, firms with low cash flow are less likely to obtain a line of credit, and they rely more heavily on cash in their corporate liquidity management. An important channel for this correlation is the use of cash flow-based financial covenants by banks that supply credit lines. I find that firms must maintain high cash flow to remain compliant with covenants, and banks restrict firm access to credit facilities in response to covenant violations. Using the cash-flow sensitivity of cash as a measure of financial constraints, I provide evidence that lack of access to a line of credit is a more statistically powerful measure of financial constraints than traditional measures used in the literature.]